“Czy przekroczyliśmy granicę?” Kilka uwag o ekologii postlacanowskiej - Turczyn, Anna (Er(r)go. Teoria - Literatura - Kultura, 2025)
This article attempts to analyze Jacques Lacan’s reflections on the ethics of desire and the subject’s relation to the object, with particular emphasis on the object of anxiety, juxtaposed with contemporary French post-Lacanian thought on ecology and climate crises. It demonstrates how ecological thinking intertwines with reflection on language and enables the creation of a new discourse, capable of addressing the effects of both capitalist and scientific models of knowledge, while fostering forms of social bonds that support the transformation of existing existential and ecological practices.